Influenza vaccination rates in children: a multicenter nationwide study - Yakın, Hacer; Aykaç, Kübra; İçöz, Sultan and Kolukırık, Halit and Gerçek, Gülce and Arslan, Ece and Demir, Osman Oğuz and Güdeloğlu Çetiz, Elif and Sinanoğlu, Muhammed Selçuk and Kaçar, Pelin and Gülderen, Mustafa and Özer, Arife and Demir Gümüş, Dilan and Erdem Torun, Şeyma and Ceylan Cura Yayla, Burcu and Kılıçaslan, Önder and Karbuz, Adem and Şener Okur, Dicle and Genceli, Mustafa and Metin Akcan, Özge and Büyüktaş Aytaç, Didem and Akkoç, Gülsen and İlbay, Sare and Güder, Latife and Bedir Demirdağ, Tuğba and Tapısız, Anıl and Şahin İzci, Eda and Dalgıç, Nazan and Aksoy, Fatma Dilşad and Çiftçi, Esra and Çelebi, Solmaz and Mete Atasever, Neslihan and Somer, Ayper and Çakmak Taşkın, Esra and İşeri Nepesov, Merve and; de, Özlem and; n, Derya and Kara, Soner Sertan and Alkan, Gülsüm and Özyalvaç, Büşra and Emiroğlu, Melike and Çakıl Güzin, Ayşe and Karadağ Öncel, Eda and Özgül Postuk, Gülben and Gayretli Aydın, Zeynep Gökçe and Yaşar, Belma and Ümit, Zuhal and Bayturan Şen, Semra and Ekemen, Coşkun and Avcu, Gülhadiye and Sınav Utku, Hatice and Öncel, Selim and Şahin, Aslıhan and Ekemen Keleş, Yıldız and Kıymet, Elif and Şenkon, Oben Gözde and Hitay Telefon, Ayşe and Kılıç Çil, Merve and Çelik, Ümit and Gökay, Nahida and Yeşil, Edanur and Kuyucu, Necdet and Bostan, Ayşenur and Mardinoğlu, Gizem and Kılıç, Ömer and Çetin, Benhur and Kara, Mesut and Erdem, Nurettin and Şahinkaya, Şahika and Coşkun, Zehra Nihan and Konca, Hatice Kübra and Kanık-Yüksek, Saliha and Karaoğlu Asrak, Hatice and Tanrıkulu, Hakan and Özlü, Canan and Dönmez, Ayşe Sena and Toy Usta, Gülizar and Çelikkan, Kıvanç and Çakıcı, Özlem and Avcı, Ezgi and Hacısoy, Aysel and Mercan, Halise and Avcı, Hanife and Cengiz, Ali Bülent and Özsürekci, Yasemin (The Turkish Journal of Pediatrics, 2026)
Background. Influenza remains a major cause of morbidity and mortality in children worldwide, yet vaccination coverage is still suboptimal in many countries. We aimed to understand parental awareness, attitudes, and determinants of vaccine uptake to guide effective strategies for increasing coverage and protecting vulnerable pediatric populations. Method. A cross-sectional study was conducted between October 2023 and May 2024 in 38 hospitals across 23 provinces in Türkiye. Data were collected from 5002 families through face-to-face interviews, with 4404 valid responses analyzed. Results. The overall influenza vaccination rate among children was 4.4% (n=195/4404). Vaccination coverage was slightly higher in high-risk groups compared to non-high-risk groups (5.2% vs. 3.5%, p=0.003). Factors positively associated with vaccination uptake included the presence of chronic illness in the child (15.1% in vaccinated vs. 4.7% in unvaccinated, p